Pengaruh Penerapan Model Problem Based Learning Terhadap Hasil Belajar dan Motivasi Belajar Peserta Didik MTsS Nurul Yaqin Benteng Kabupaten Kepulauan Selayar - Nurmiati Nurmiati; Firdaus Daud; Muhammad Danial (UNM Journal of Biological Education, 2022)
The study is a quasi-experimental research (quasi-experimental design) which aims to examine the influence of Problem Based Learning model on learning outcomes and students’ learning motivation at MTsS Nurul Yaqin Benteng in Selayar Islands district. The population in this study were all students of MTsS Nurul Yaqin Benteng of grade VIII for academic year of 2021/2022. Samples were taken by using Random Sample technique. The learning motivation data were collected by using learning motivation questionnaire; whereas, the learning outcomes data were collected by using multiple choice test. Data were analyzed by employing descriptive analysis and t-test on SPSS version 23.0. The results of the study reveal that the students who were taught by using the Problem Based Learning model experienced an increase in learning outcomes which is in high category. Meanwhile, the students who were taught by using direct learning also experienced an increase in learning outcomes and learning motivation which is in high category. The results of hypothesis testing using the t-test show the learning outcomes sig (2-tailed) > α 0.05 or 0.000 > α 0.05. H0 is rejected and H1 is accepted. Based on the test criteria, it can be concluded that there is an influence of implementing the Problem Based Learning model on learning outcomes and students’ learning motivation on Human Digestive System material in grade VIII at MTsS Nurul Yaqin Benteng in Selayar Islands district.